Indoor Positioning Techniques and Approaches for WI-FI Based Systems - Abusara, Ayah Mahmoud (2015)
A Master of Science thesis in Electrical Engineering by Ayah Mahmoud Abusara entitled, "Indoor Positioning Techniques and Approaches for WI-FI Based Systems," submitted in June 2015. Thesis advisor is Dr. Mohamed Hassan. Soft and hard copy available.